(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
Over the past two decades, organic food production system was transformed from a loosely coordinated network of local producers and consumers, into a globalized system that defines formally regulated trade that links socially and spatially distant places of production and consumption. Customers today are more informed on food production, genetic manipulation and the impact of food on health, through a variety of information channels (fairs, events marketing, Internet, etc.). Therefore, today it is not enough to meet the basic needs of hedonistic consumer, because it cannot be enough to motivate the customer. The product has to arouse the customer added values that are important for his choice. Organically grown food, among other things, offers the following added value: better taste, food safety for the customer and his family, the use of packaging and production methods that have less impact on the environment. Today, organically grown food is increasingly prevalent in supermarkets, as well as in specialized stores, whose number is growing on the Croatian market. It is encouraging that organic farmers began procedures for obtaining eco sign. More and more people are turning to so-called "healthy" lifestyle. This work is based on research habits of buying organic products among the consumers in the area of Koprivnica – Križevci County on a sample of 165 respondents. The aim of the research was to determine how the participants at all are familiar with the concept of organic farming, lifestyle and diet, and consuming the same. Also, we will provide the environmental, economic and socio-cultural well-being of organic farming, that today, because of the immense depth and the devastation of the environment should be more relevant than ever. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.